Characterization of physico-chemical and bio-chemical compositions of selected four strawberry cultivars - Xiamin Cao; Yongtao Wang; Xiaojun Liao; Xiaosong Hu (Journal of Applied Botany and Food Quality, 2018)
The physico-chemical and bio-chemical compositions of Hongyan, Tiangxiang, Tongzi Ι and Zhangji strawberries inChinawere analyzed. Their values were pH 3.42~3.73, titration acidity 0.63~0.79%, total soluble sugars 5.26~8.95 g/100 gfresh weight (FW), ascorbic acid 21.38~42.89 mg/100 gFW, total phenolics 235.12~444.73 mg/100 gFW, pectin 82.84~96.13 mg/100 gFW, total organic acids 874.30~1216.27 mg/100 gFW, Individual phenolic compounds other than anthocyanins 7.60~12.18 mg/100 gFW, free amino acids 13.35~32.66 mg/100 gFW, monomeric anthocyanins 4.47~47.19 mg/100gFW, antioxidant capacity of ·DPPH 14.14~18.87 and FRAP 7.97~10.54 equal to mg/100 gVc, polyphenol oxidase (PPO) activity 0~0.42 Abs/min, peroxidase (POD) activity 0.17~0.34 Abs/min and pectin methyl esterase (PME) activity 0.012~0.018 mL/min. Tongzi Ι was most suitable for food processing due to the highest titration acidity, total phenolics, pectin, total organic acids, monomeric anthocyanins, antioxidant capacity of ·DPPH and FRAP with lower PPO, POD and PME activity.